Defying Maliseet Language Death : Emergent Vitalities of Language, Culture, and Identity in Eastern Canada. - Perley, Bernard C. (UNP - Nebraska, 2011)
Published through the Recovering Languages and Literacies of the Americas initiative, supported by the Andrew W. Mellon Foundation Today, Indigenous communities throughout North America are grappling with the dual issues of language loss and revitalization. While many communities are making efforts to bring their traditional languages back through educational programs, for some communities these efforts are not enough or have come too late to stem the tide of language death, which occurs when there are no remaining fluent speakers and the language is no longer used in regular communication. Th.